PENGARUH AUDIT TENURE, FEE AUDIT, UKURAN KANTOR AKUNTAN PUBLIK, SPESIALISASI AUDITOR, KOMITE AUDIT TERHADAP KUALITAS AUDIT - Rafif Ivan Hartono; Herry Laksito (Diponegoro Journal of Accounting, 2022)
This study aims to determine the effect of Audit Tenure, Audit Fee, Public Accounting Firm Size, Auditor Specialization, and Audit Committee on Audit Quality. The Audit Tenure variable is proxied by how long a KAP carries out audit duties on a client, the Audit Fee variable is proxied by the natural logarithm of professional fees, KAP size is proxied by the Big four and non-Big four KAP types, Auditor Specialization is proxied by the auditor's control over market share with a limit of 15%, and the Audit Committee is proxied by the existence of an audit committee in a company. Audit Quality variable is proxied by Going Concern Opinion (score 1) and Non-Going Concern Opinion (score 0). This study uses data from companies in the energy industry listed on the IDX between 2016 and 2019. Of the 229 samples that meet the criteria, 37 companies can be categorized as receiving going concern opinions and 192 receiving non-going concerns opinions. Statistical testing was carried out using Logistic Regression with the help of SPSS version 25 computer program. The results of this study indicate that only the size of the public accounting firm has a positive influence on audit quality, while audit tenure, audit fees, auditor specialization, and audit committee have no effect on audit quality.